2020
DOI: 10.3390/pharmaceutics12020152
|View full text |Cite
|
Sign up to set email alerts
|

Alternatives to Biological Skin in Permeation Studies: Current Trends and Possibilities

Abstract: The transdermal route of drugs has received increased attention in recent years due to numerous advantages over the oral and injectable routes, such as avoidance of the hepatic metabolism, protection of drugs from the gastrointestinal tract, sustained drug delivery, and good patient compliance. The assessment of ex vivo permeation during the pharmaceutical development process helps in understanding the product quality and performance of a transdermal delivery system. Generally, excised human skin relevant to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
130
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(163 citation statements)
references
References 113 publications
0
130
0
1
Order By: Relevance
“…The use of an infinite dose not only enabled identifying the realistic mechanism behind the penetration and permeation of the studied siloxanes, but is used when no such research has been carried out so far. We would also like to point out that according to the guidelines of OECD and WHO, ex vivo human skin studies are the gold standard for transdermal research, and can demonstrate the closest relationship with the in vivo processes [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…The use of an infinite dose not only enabled identifying the realistic mechanism behind the penetration and permeation of the studied siloxanes, but is used when no such research has been carried out so far. We would also like to point out that according to the guidelines of OECD and WHO, ex vivo human skin studies are the gold standard for transdermal research, and can demonstrate the closest relationship with the in vivo processes [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, it has been found that simple artificial membranes do not match the characteristics of the skin and, consequently, their use is suggested only in the determination of drug release. Therefore, there is a growing demand for new artificial membranes that model the human skin well to provide relevant and useful results in predicting the permeation of the drug from the dermal drug delivery preparations [1,11].…”
Section: Introductionmentioning
confidence: 99%
“…The limitation of this epiCS model is the lack of a dermal part although the fibroblasts very seldom play a metabolically active role—they are mostly active in wound healing processes ( Chang et al., 2002 ). Besides, the stratum corneum on any reconstructed skin model is likely more permeable than actual intact human skin ( Neupane et al., 2020 ). Novel methods recently became available which are capable of delivering larger substances (peptides and proteins) through the skin ( Asselineau et al., 1990 ; Prow et al., 2011 ).…”
Section: Discussionmentioning
confidence: 99%